Understanding the impact of behavioral biases and financial literacy on investment choices: Evidence from Southeast Sulawesi - Bahari, Samsul; Suriadi, Suriadi; Jasiyah, Rabiyatul; Fadli, Andi Muh Dzul; Hasddin, Hasddin (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
In Southeast Sulawesi, investment decision-making has increasingly been influenced by behavioral factors, amid dynamic trends in foreign direct investment (PMA) and domestic investment (PMDN). A nuanced understanding of how cognitive and emotional tendencies shape financial decisions is essential to designing more effective and inclusive investment strategies. This study investigates the impact of cognitive and emotional biases on financial literacy and investment behavior, while also exploring the mediating role of financial literacy. Employing an explanatory research design, the study surveyed individual investors registered with the Indonesia Stock Exchange in Southeast Sulawesi, numbering 17,354, with 391 respondents randomly selected and 276 providing valid responses (70.58%). Data were analyzed using Partial Least Squares–Structural Equation Modeling (SEM-PLS). Findings reveal that both cognitive and emotional biases substantially affect financial literacy, which in turn positively influences investment decisions. Empirical data from 2009 to 2023 show that investors with higher financial literacy are more capable of evaluating and responding to fluctuations in PMA and PMDN, thereby contributing to both foreign and domestic investment growth. These results highlight that mitigating behavioral biases and enhancing financial literacy are critical for improving investment outcomes and sustaining balanced development in regional investment activities.